Antecedents of retail patronage in cooperative retail context. Issue 2 (December 2018) - Juga, Jari; Juntunen, Jouni
Highlights: Despite the importance of cooperative retail businesses, there is little research related to the impact of cooperative values on buying behavior. Attitudes toward cooperative retail are relatively favorable, while the awareness of retailers' cooperative oriented communication is modest. Consumers' attitudes and retailers' communications regarding cooperative business affect the consumers' patronage. .Cooperative oriented communication has a strong impact on patronage, underlining the retailer's role in promoting the cooperative retail model. Abstract: This study aims to shed light on the antecedents of consumers' buying behavior in a cooperative retail context. More specifically, the goal is to analyze the influence of consumers' cooperative oriented attitudes and the retailer's cooperative oriented communication on the consumer's retail patronage. The study is based on an empirical survey of members of a Finnish retail cooperative in 2017. The findings show that the attitudes towards the cooperative retail model are relatively favorable, whereas the awareness of the retailers' cooperative oriented communication is less pronounced. However, the impact of cooperative oriented communication on patronage appears to be strong, which underlines the retailer's active role in promoting the cooperative retail model to the consumers.